1975
DOI: 10.1073/pnas.72.11.4459
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of isolated smooth muscle cells by inophore A23187.

Abstract: Ionophore A23187 causes contraction of smooth muscle cells isolated from the stomach muscularis of Bufo marinus. The peak response is reached within 10 sec of ionophore addition and then decays to a lesser, sustained contraction. The initial phase of contraction is maximal at A23187 concentrations greater than 5 X 10-6 M and half maximal at 5 X 10-7 M. Chelation of extracellular calcium b ethyleneglycol-bis(,-aminoethylether)NN'-tetraacetic acid (EGTA) does not affect the initial contraction produced by A23187… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In pancreatic fragments membrane depolarization of surface cells occurs within minutes of A23187 application (Poulsen & Williams, 1976). Similarly, other actions such as calcium uptake and triggering of exocytosis in mast cells (Foreman etal., 1973;Cochrane & Douglas, 1974), contraction of isolated smooth muscle cells (Murray et al, 1975), activation of sea urchin eggs (Steinhardt & Epel, 1974), and insulin release by perifused islets (Karl et al, 1975) are initiated within seconds to minutes of ionophore addition. Because almost all of these rapid actions involve isolated cells or superficially located cells, it is tempting to speculate that the availability of ionophore to interior cells of tissue fragments is limited by physical exclusion of ionophore particles as well as slower membrane uptake of chelated A23187.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In pancreatic fragments membrane depolarization of surface cells occurs within minutes of A23187 application (Poulsen & Williams, 1976). Similarly, other actions such as calcium uptake and triggering of exocytosis in mast cells (Foreman etal., 1973;Cochrane & Douglas, 1974), contraction of isolated smooth muscle cells (Murray et al, 1975), activation of sea urchin eggs (Steinhardt & Epel, 1974), and insulin release by perifused islets (Karl et al, 1975) are initiated within seconds to minutes of ionophore addition. Because almost all of these rapid actions involve isolated cells or superficially located cells, it is tempting to speculate that the availability of ionophore to interior cells of tissue fragments is limited by physical exclusion of ionophore particles as well as slower membrane uptake of chelated A23187.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, many compounds which incorporate into membranes such as ionophores (X-537A), mitochondrial uncouplers (DNP, FCCP), or fluorescent probes (ANS, chlortetracycline) have been localized or are known to act on intracellular organelles as well as the plasma membrane. No studies have dealt with intracellular uptake of A23187 directly, but the fact that A23187 can release calcium from sarcoplasmic reticulum vesicles and isolated mitochondria (Caswell & Pressman, 1972;Reed & Lardy, 1972b;Scarpa, Baldassare, & Inesi, 1972;Wong etal., 1973;Sordahl, 1975;Binet & Volfin, 1975) and the finding that A23187 can induce secretion or contraction in some cells in the absence of extracellular calcium (Hainaut & Desmedt, 1974;Schroeder & Strickland, 1974;Steinhardt & Epel, 1974;Ashby & Speake, 1975;Charles etal., 1975;Karl etal., 1975;Murray, Reed, & Fay, 1975) suggest that the ionophore is able to release intracellular calcium.…”
mentioning
confidence: 98%
“…In excess K + solution the K + channel opener nicorandil fails to induce hyperpolarisation in cardiac (Yanagisawa and Taira 1980) and smooth muscle (Furukawa et al 1981), because in such solutions the membrane potential is coincident with the K + equilibrium potential. A23187 is generally believed to be a divalent, cationselective ionophore which forms complexes with Ca z+ and Mg 2÷, thus facilitating their diffusion through various membranes and inducing contraction of smooth muscle (Triggle et al 1975;Murray et al 1975;Asano and Hidaka 1984). This study shows the different effects seen with KRN4884, levcromakalim and nifedipine.…”
Section: Methodsmentioning
confidence: 99%
“…A23187 produces a contraction which is dependent on the external Ca2+ in some smooth muscles (Swamy et al 1975;Mandrek & Golenhofen, 1977;Ishida & Shibata, 1980) but does not function solely by increasing the permeability ofthe cell membrane to Ca2+ in vascular smooth muscles (Watson, 1978). Murray, Reed & Fay (1975) reported that in isolated stomach smooth muscle cells of Bufo marines, A23187 produced an initial EGTA-insensitive contraction and a sustained, secondary Ca2+-sensitive contraction. Saida (1981) found that this agent skinned the fibres of guinea-pig taenia coli, after extended application.…”
Section: Introductionmentioning
confidence: 99%